Crystal and molecular structure of bis(4-bromo-N-(di-n-butylcarbamothioyl)benzamido) copper(II) complex - Binzet, Gun; Flörke, Ulrich; Külcü, Nevzat; Arslan, Hakan (European Journal of Chemistry, 2012)
The title compound, C32H44Br2CuN4O2S2, was synthesized from 4-bromo-N-(dibutylcarbamothioyl)benzamide ligand and copper(II)acetate. The crystal structure of bis(4-bromo-N-(di-n-butylcarbamothioyl)benzamido) copper(II) complex was determined from single crystal X-ray diffraction studies. It crystallizes in the triclinic space group, P-1 (no. 2) with unit cell dimensions of a = 8.519(10) Å, b = 16.64(2) Å, c = 25.78(4) Å, α = 77.11(3)o, β = 85.59(3)o, γ = 89.46(2)o , Z = 4 and V = 795.8(6) Å3. The crystal structure is stabilized by weak C-H…N, C-H…S and C-H…Br hydrogen-bonding interactions.